Mould, unpacking toxic shame with making of diaristic photobook - Lin, Shiauyu (Nanyang Technological University, 2020)
Mould demonstrate the making of photobook as a therapeutic process that helps in confronting unresolved personal issues of toxic shame, unpacking the layered coping mechanisms and symptoms, and finding new perspective to the problem. Referencing the theories used by art therapy and narrative therapy practice, this essay will introduce the characteristics of photobooks, and elaborate on the therapeutic process of photography and making photobooks.